Perlindungan Konsumen atas Penggunaan Bahan Tambahan Pangan pada Makanan dan Minuman - Hanari Fajarini; Anggray Duvita Wahyani (Kosmik Hukum, 2020)
Food circulation that does not meet health standards is generally caused by the desire of producers to get the maximum profit by neglecting consumer safety. Lack of legal protection for consumers results in consumers in a weak position. The purpose of this study was to determine how the legal protection of consumers for the use of food additives. The method or approach used in this research is sociological with a qualitative paradigm, in which sociology is an approach with the aim of studying and examining the existence of a phenomenon of reciprocal relations between law and other social institutions in which law is not conceptualized as a form of independent (autonomous) normative symptoms. , but as a social institution which is related significantly to other variables. The results showed that 80% of business operators use synthetic dyes, while only 20% of business operators use natural dyes. Meanwhile, the results of interviews with consumers showed that 63.33% of the consumer's benchmark in choosing food was food with a more striking color, while 36.67% of consumers chose food that had no striking color. The results showed that to protect consumers from the use of food additives, there are several efforts that can be made, namely supervision, guidance and consumer education. The conclusion of this research is to realize legal protection for consumers, every food product is required to meet food safety and quality standards, as regulated in Article 111 of the Law on Health.Keywords: food, food additives, consumer protection